KERAGAMAN MOLEKUL, POLA KIMIA, DAN HUBUNGAN BIOGENESIS SENYAWA-SENYAWA DARI TUMBUHAN AGLAIA DAN DYSOXYLUM (MELIACEAE) - Tukiran, (Matematika dan Sains, 2010)
Some non phenolic and phenolic compounds had been isolated for the first time from n-hexane and chloroform extracts of stem bark of Meliaceae plants, namely Aglaia odorata, Aglaia odoratissima, Aglaia elaeagnoidea and Dysoxylum gaudichandianum. These structures had been established based on spectroscopic data (UV-Vis, IR, NMR, FABMS and GC-MS). These isolated compounds had been studied about chemical diversity, chemical pattern and biogenetic relationship in the plants.